Fostering students’ speaking performance through the Show and Tell technique - Nurfadhilawati S. Halaco; Konder Manurung; Mashuri Mashuri; Abdul Kamaruddin (University of Muhammadiyah Malang, 2025)
This study explores the impact of the Show and Tell technique on students’ speaking ability and confidence in English learning. A quasi-experimental design was used to compare two groups of students from a public senior high school in Palu, Central Sulawesi: an experimental group taught using the Show and Tell method, and a control group not taught using this method. Both groups completed pre- and post-tests to measure their speaking skills, including fluency, comprehension and accuracy. The findings reveal that the experimental group outperformed the control group, scoring about ten points higher in the post-test. A Mann-Whitney test (Asymp. Sig. = 0.001) confirmed this difference as statistically significant. These results suggest that Show and Tell is more than just a classroom activity: it not only enhances fluency, comprehension, and accuracy but also encourages students to speak up more actively. In practice, this highlights the value of interactive learning strategies in creating a supportive classroom environment where students feel safe to try, make mistakes, and improve. This study contributes to the field of English language teaching by providing empirical evidence that the Show and Tell technique effectively integrates affective and linguistic development, promoting communicative competence in EFL contexts. Teachers are therefore encouraged to adopt Show and Tell as a practical tool to help students develop their speaking skills more effectively